Electrodeposition Assisted Dynamic Assemblies of Chitosan/Alginate Composite Multi-Membrane. Issue 1 (March 2020) - Xu, Feiyang; Wang, Dong; Yan, Kun
Abstract: Electrodeposition of natural polymer as an effective approach to improve bioactivity of the conductive substrate has receives much attentions in medical and other applications. In this work, we developed a novel chitosan/alginate (CS/ALG) multi-membrane on titanium plate via the electrodeposition assisted dynamic assembly approach. Specifically, the electrical signal induced CS coating can serve as a versatile platform for layer by layer assemblies of ALG into the multi-membrane through strong electrostatic interaction. The prepared multi-membranes exhibit great swelling performance and excellent mechanical properties at dried states, with the tensile stress and strain values reaching to 58.2 MPa and 4.25 % for the 10 layers sample. In summary, we believe such green, low cost and rapid fabrication approach and mild processing environment would spur great potential for construction of multi-functional coating and smart drug elution system on the conductive implants.